1989
DOI: 10.1152/ajpregu.1989.257.6.r1488
|View full text |Cite
|
Sign up to set email alerts
|

Methane production in ruminants: its effect on the doubly labeled water method

Abstract: The doubly labeled water (DLW) technique for measuring CO2 production (rCO2) in free-living animals requires an assessment of the elimination of both 2H and 18O from the body over a long period of time. To calculate rCO2, it is necessary to calculate water turnover (rH2O) from the 2H flux rate. In ruminant animals, the accuracy of this calculation is affected by the loss of 2H in methane. We have quantified the effect of methane production (rCH4) on the 2H flux rate, determined in four sheep given 2H2O. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 0 publications
2
35
1
3
Order By: Relevance
“…To calculate the effect of methanogenesis on the DLW method it is necessary to know the rate of CH 4 production (rCH 4 ) and the stoichiometry of water H incorporation into CH 4 . Midwood et al (1989) have shown that each litre of CH 4 produced will cause rH 2 O to be overestimated by 1 . 052 g and rCO 2 to be underestimated by 0 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To calculate the effect of methanogenesis on the DLW method it is necessary to know the rate of CH 4 production (rCH 4 ) and the stoichiometry of water H incorporation into CH 4 . Midwood et al (1989) have shown that each litre of CH 4 produced will cause rH 2 O to be overestimated by 1 . 052 g and rCO 2 to be underestimated by 0 .…”
Section: Resultsmentioning
confidence: 99%
“…629 litres. These authors suggested that rCH 4 may be calculated from an estimate of rCO 2 since the rCO 2 :rCH 4 ratio is relatively stable, falling between 10 and 20 for a wide range of animals fed at or above maintenance on very different diets with forage:concentrate ratios of 100:0 through to 20:80 (Midwood et al 1989). For example, Brockway & Maloiy (1967) measured an approximate rCO 2 :CH 4 ratio of 16 in red deer consuming chopped hay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Para a estimativa de produção de metano (Midwood et al, 1989(Midwood et al, , 1993 O calculo do N microbiano é apresentado na equação abaixo:…”
Section: Coleta De Urina E Produção Microbianaunclassified